The Dual Nature of Representative Dynamics in Brazilian Public Policy Conferences: An Analysis of the Conferences on Health, Social Assistance and Policy for Women. Issue 3 (3rd July 2019) - Faria, Claudia Feres; da Silva, Eduardo Moreira; Lins, Isabella Lourenço
ABSTRACT: This article investigates the dual nature of representative dynamics in Public Policy Conferences (PPCs) in Brazil. PPCs are democratic innovations that expand the participation and deliberation from the local to the national level of the Federative Republic of Brazil through the representation of people and policy proposals. This article states that representative practices promote both exclusive and inclusive dynamics, which are explained by the procedures for selecting delegates and policy proposals. To support this statement, we analyse (1) the socioeconomic and political profiles of the participants; (2) the policy proposals; (3) the perception of the participants on the publicity and accountability practices; and, (4) the recognition of representative practices through the perception of the participants on the implementation of the proposals, as well as the willingness and motivation to continue participating. The data comes from the analysis of internal procedures of health, social assistance and policy for women conferences, and from a survey conducted in 2014 with 1, 066 participants in Belo Horizonte and in Minas Gerais. Data analysis allows us to sustain that, although the change of territorial levels impacts the PPCs, it does not compromise their democratic quality.